Management of retroperitoneal lymph nodes in advanced ovarian cancer. (1st February 2008) - Hacker, N. F.; Valmadre, S.; Robertson, G.
Abstract : Autopsy studies have demonstrated a very high incidence of positive retroperitoneal lymph nodes in patients with advanced ovarian cancer, but the clinical management of these nodes has only recently been investigated. Several institutional studies had suggested an advantage to systematic removal of pelvic and paraaortic nodes in patients whose tumor was optimally cytoreduced in the peritoneal cavity. However, the only randomized prospective study revealed a 7-month benefit in progression-free survival for patients having systematic lymphadenectomy, but no benefit in terms of overall survival. Unless a future randomized trial shows evidence to the contrary, removal of clinically normal nodes should not be considered part of the standard care for patients with advanced ovarian cancer. Bulky nodes should be removed as part of the surgical aim of removing all macroscopic residual disease